Haptic Links: Bimanual Haptics for Virtual Reality Using Variable Stiffness Actuation - Strasnick, Evan; Holz, Christian; Ofek, Eyal; Sinclair, Mike; Benko, Hrvoje (CHI 2018/SIGCHI 2018, 2018)
We present Haptic Links, electro-mechanically actuated physical connections capable of rendering variable stiffness between two commodity handheld virtual reality (VR) controllers. When attached, Haptic Links can dynamically alter the forces perceived between the user’s hands to support the haptic rendering of a variety of two-handed objects and interactions. They can rigidly lock controllers in an arbitrary configuration, constrain specific degrees of freedom or directions of motion, and dynamically set stiffness along a continuous range. We demonstrate and compare three prototype Haptic Links: Chain, Layer-Hinge, and Ratchet-Hinge. We then describe interaction techniques and scenarios leveraging the capabilities of each. Our user evaluation results confirm that users can perceive many two-handed objects or interactions as more realistic with Haptic Links than with typical unlinked VR controllers.